Neurosurgery for Optic Pathway Glioma: Optimizing Multidisciplinary Management - Samples, Derek C.; Mulcahy Levy, Jean M.; Hankinson, Todd C. (Frontiers in Surgery, 2022)
Optic pathway glioma (OPG) comprises 10% of pediatric brain tumors and 40% of all pediatric low-grade gliomas (pLGGs). While generally considered benign pathologically, many require interventions with chemotherapy, radiation, or targeted therapies. Management has historically foregone tissue diagnosis given the classical clinical/radiographic presentation of these tumors, inability to safely remove the lesions surgically, and efficacy and safety of available chemotherapy options. Furthermore, when considering such aspects as their delicate location, the role of surgery continues to be heavily debated. More recently, however, a greater understanding of the genetic drivers of OPGs has made operative tissue sampling a critical step in management planning, specifically for patients without Neurofibromatosis, Type I (NF1). Given the need for long-term, complex management of pediatric OPGs, it is crucial that a multidisciplinary approach is employed, and the rapidly expanding role of molecular characterization be incorporated into their management.